Gender aspect of research of emotional intelligence of teenagers - Yu V Davydova (Peoples' Friendship University of Russia (RUDN University), 2010)
Different views on gender distinctions in emotional sphere of a person are analyzed in the article, and also results of empirical research of gender distinctions in sphere of emotional intelligence of teenagers are presented.